The Role Of Bullion Banks As A Market Risk Management Instrument In Indonesia'S Gold Sector - Ratih Hastasari; Suharini Suharini (Jurnal Ilmiah Multidisiplin, 2025)
Gold has long been regarded as a safe haven asset capable of maintaining value stability amid economic uncertainty. Bullion banks emerge as a strategic solution to manage risks in the gold market by offering services such as hedging, clearing, storage, and gold-based financing. This study aims to analyze the potential role of bullion banks in mitigating gold market risks in Indonesia and to assess their implementation readiness. Using a descriptive qualitative approach through literature review, the study reveals that bullion banks can enhance transaction security, market liquidity, and export-import efficiency in the gold sector. However, several challenges persist, including inadequate clearing infrastructure, fragmented regulations, and limited public awareness. The involvement of government institutions and Islamic financial institutions such as Bank Syariah Indonesia plays a crucial role in establishing a resilient bullion banking system. With integrated policies, technological advancement, and cross-sector collaboration, bullion banks can significantly strengthen Indonesia’s gold market resilience and transparency.